1971
DOI: 10.1073/pnas.68.4.810
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Sites for Calcium Ion Binding to Elastin and Collagen: A Charge Neutralization Theory for Calcification and Its Relationship to Atherosclerosis

Abstract: Neutral, uncharged binding sites for calcium ions are proposed for elastin and collagen. The sites utilize, particularly from a conformational viewpoint, the most striking feature of the amino acid composition, that is, the high glycine content. Glycines favor the formation of B-turns and associated conformations that are known, from studies on ion-transporting antibiotics, to interact with cations. By analogy with certain antibiotics, which are uncharged polypeptides and depsipeptides that bind cations by coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…Also, this model most likely allows elucidation of the important sites of these TE reactions by using mutant TE. We have reported that tropoelastin downregulates the induction of calcification via the elastin receptor (manuscript in submission), although the pathway of the inhibitory reaction by TE on calcification presents several candidate reactions such as the activation of signal transduction via the elastin receptor (33) and the binding of calcium by tropoelastin molecule (6,7). Moreover, it has been reported that TE has a variety of biological effects which are mediated by the elastin receptor, chemotactic cell migration, modulation of ion flux, adhesion of cells to elastin fibers, tumor cellmatrix interaction, elastase synthesis and release, free radical production, endothelium and nitric oxide-mediated vasorelaxation, chaperon for elastogenesis, lymphocyte proliferation, apoptotic cell death (34)(35)(36)(37)(38) as well as properties as a major elastic fiber component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this model most likely allows elucidation of the important sites of these TE reactions by using mutant TE. We have reported that tropoelastin downregulates the induction of calcification via the elastin receptor (manuscript in submission), although the pathway of the inhibitory reaction by TE on calcification presents several candidate reactions such as the activation of signal transduction via the elastin receptor (33) and the binding of calcium by tropoelastin molecule (6,7). Moreover, it has been reported that TE has a variety of biological effects which are mediated by the elastin receptor, chemotactic cell migration, modulation of ion flux, adhesion of cells to elastin fibers, tumor cellmatrix interaction, elastase synthesis and release, free radical production, endothelium and nitric oxide-mediated vasorelaxation, chaperon for elastogenesis, lymphocyte proliferation, apoptotic cell death (34)(35)(36)(37)(38) as well as properties as a major elastic fiber component.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these changes, vascular calcification causes physical changes such as decreased elasticity of vessels, which is partly responsible for disorders related to elastic fibers (4). Previous reports have demonstrated that calcium deposition occurs along elastic fibers in vascular calcification (5) and that the properties of elastin include calcium binding activity (6,7). We have already reported that calcium deposition is found predominantly in autoclaving-resistent elastin fractions in rat-calcified models (8).…”
Section: Introductionmentioning
confidence: 96%
“…Previous reports have demonstrated calcium deposition along elastic fibers in vascular calcification (27), and it has been shown that one property of elastin is calcium binding activity (28)(29)(30)(31). We have already reported that calcium deposition can be clearly observed in autoclaving-resistant elastin fractions using an in vivo calcified model (32,33).…”
Section: Abstract: Tropoelastin Vascular Calcification Elastin Binmentioning
confidence: 58%
“…It may be a result of production of abnormal elastic fibers, alteration in the extracellular matrix, or degeneration of elastic fibers [36]. This calcification is part of the aging process and is in part responsible for arterosclerotic changes [35].…”
Section: Discussionmentioning
confidence: 99%